The Cantor's Son - Motyleff, Ilya; Goldin, Sidney M.; Zucker, Frank; Oysher, Moishe; Weiss, Florence; Abarbanell, Judith (The National Center for Jewish Film, 2006)
This Yiddish feature film musical drama marks the screen debut of singer and cantor Moishe Oysher ("Overture to Glory" and "The Singing Blacksmith"). Shot in Pennsylvania near the Pocono Mountains, the film features Oysher in the title role of a wayward youth who makes his way from his Polish shtetl to New York's Lower East Side (the film includes rare glimpses of the Lower East Side and of 2nd Avenue Yiddish theater marquees of the period). While washing floors in a nightclub several years later he is "discovered" and becomes a well-known singer. Ultimately, Oysher's character returns home to the Old Country and reunites with his parents and his childhood sweetheart. In his book on Yiddish cinema "Bridge of Light", critic J. Hoberman calls "The Cantor's Son" an "anti-Jazz Singer," further remarking that the film's story parallels Oysher's own struggle to reconcile his cantorial calling with a career in show business. Like his film character, Oysher, born in Bessarabia the son and grandson of cantors, was both a matinee idol and a celebrated cantor. Oysher was married to his co-star Florence Weiss. After film director Sidney M. Goldin ("Uncle Moses", "East and West") suffered a fatal heart attack during the production of "The Cantor's Son", he was replaced by Stanislavsky-protege Ilya Motlyeff, who is credited as the film's director. The film's score (including the sentimental song "Mayn Shtetele Betz") was composed by Alexander Olshanetsky, a concert violinist and veteran of the 2nd Avenue Yiddish theater. [jewishfilm.org]